EXPERIENCE OF TREATMENT WITH ABATACEPT IN PATIENTS WITH JUVENILE RHEUMATOID ARTHRITIS - Ye. I. Alekseyeva; S. I. Valiyeva; T. V. Sleptsova ("Paediatrician" Publishers LLC, 2011)
The article presents a case report of a patient with juvenile rheumatoid arthritis refractory to the treatment with metothrexate. Combined therapy with metothrexate and leflunomide induced development of unfavorable effects resulted in cancellation of leflunomide. Successful administration of biological agent inhibitor of T-lymphocytes co-stimulation abatacept is described. Treatment with abatacept resulted in remission of a disease; it increased patient and her family's quality of life.